The Role of Chinese Society in the Economic and Cultural Dynamics of the Archipelago: A Historical Study through Interpretation and Analysis of Historical Facts - Rohman, Holilur; Zuhdi, Achmad (Proceedings of International Conference on Islamic Civilization and Humanities, 2026)
This article discusses the role of the Chinese community in the economic and cultural dynamics of the Nusantara through a historical research approach emphasizing interpretation and analysis of historical facts. The purpose of this study is to explain the contribution of the Chinese community to economic development, trade networks, and the formation of Nusantara culture from the pre-colonial period to modern Indonesia. This research applies the historical method consisting of heuristics, source criticism, interpretation, and historiography by utilizing relevant and authoritative references. The findings indicate that the Chinese community played an important role as traders, intermediaries in regional economic networks, developers of business sectors, and participants in the process of cultural acculturation in the Nusantara. In addition, the Chinese community also faced various socio-political dynamics caused by colonial policies, state discrimination, and ethnic stereotypes throughout Indonesian history. Through interpretation of various historical facts, this article affirms that the Chinese community constitutes an important element in shaping Indonesia’s economic structure and multicultural identity. Therefore, the history of the Chinese community should be understood objectively as an integral part of the formation of Nusantara civilization.